Process for making hydrophilic surface and heat spreader
Through laser processing, the hydrophilic performance of the stainless steel liquid absorbing core is improved, and the problem of limited hydrophilic performance in the prior art is solved, and more efficient water climbing and production efficiency is achieved.
Patent Information
- Application Number
- CN202510123196.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-04
AI Technical Summary
The existing stainless steel liquid absorbent core has limited hydrophilic properties and cannot meet the needs of higher energy heat dissipation.
Using laser processing technology, dense and sparse areas are alternately distributed along the first and second directions to form an alternatingly distributed substrate to improve the hydrophilic properties of the substrate.
Laser processing reduces the structural superposition effect, improves the climbing ability of water, significantly improves the hydrophilic performance of the substrate, and improves the production efficiency.
Smart Images

Figure CN119747890A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of liquid wick manufacturing, and in particular to a process method for manufacturing a hydrophilic surface and a heat spreader. Background Art
[0002] At present, the common structure of traditional heat spreaders is composed of three parts: upper and lower covers and liquid wicks. People have done a lot of research and testing by improving the process of liquid wick nets, but there is relatively little research on material covers. At present, stainless steel is widely used in the preparation of liquid wicks due to its low price, stable properties and good hydrophilic properties. The liquid wick has good heat dissipation performance. It mainly relies on the stainless steel liquid wick to quickly absorb liquid and form reflux with the heat spreader to quickly absorb and disperse the heat. As the battery capacity and chip heat dissipation energy demand increase, the stainless steel liquid wick needs to absorb the reflux liquid faster and have stronger heat dissipation capacity to meet the higher energy heat dissipation needs. Therefore, improving the hydrophilicity of stainless steel liquid wicks is a current research hotspot.
[0003] In the related art, the hydrophilicity of the stainless steel absorbent core comes from sintering it on a substrate. During the sintering process, the hydrophobic impurities on the surface of the stainless steel absorbent core are removed by high temperature. Its own structure has a certain hydrophilicity, but the hydrophilicity is limited, and the stainless steel mesh as the main component of the absorbent core seems to be irreplaceable. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a process for making a hydrophilic surface, which can make a hydrophilic surface and improve production efficiency.
[0005] A heat spreader manufactured using the above process for manufacturing a hydrophilic surface is also proposed.
[0006] The process for making a hydrophilic surface according to the first aspect of the present invention comprises:
[0007] The laser processes the surface of the substrate along a first direction;
[0008] The laser processing area along the first direction includes a first dense area and a first sparse area that are alternately distributed, and the interval between laser paths in the first dense area is smaller than the interval between laser paths in the first sparse area.
[0009] The process method for making a hydrophilic surface according to the embodiment of the first aspect of the present invention has at least the following beneficial effects: the first dense area and the first sparse area are processed by laser, so that the laser path is densely and sparsely alternatingly distributed, reducing the structural superposition effect between the laser paths, reserving sufficient space for the climbing of water, and further improving the hydrophilic performance; and, the number of laser paths that the laser needs to travel is smaller, the laser processing efficiency is higher, and the production efficiency is higher.
[0010] According to some embodiments of the present invention, the processing spacing of the first dense area is 1L-3L;
[0011] The processing spacing of the first sparse area is 6L-10L;
[0012] L: The spot diameter of the laser after focusing.
[0013] According to some embodiments of the present invention, the processing spacing of the first dense area is 0.075 mm-0.105 mm;
[0014] The processing spacing of the first sparse area is 0.5mm-0.7mm.
[0015] According to some embodiments of the present invention, the further comprising:
[0016] The laser processes the surface of the substrate along a second direction;
[0017] The second direction is perpendicular to the first direction, the processing area of the laser along the second direction includes a second dense area and a second sparse area that are alternately distributed, and the interval between the laser paths in the second dense area is smaller than the interval between the laser paths in the second sparse area.
[0018] According to some embodiments of the present invention, the moving speed of the laser is 500 mm / s-2000 mm / s.
[0019] According to some embodiments of the present invention, the further comprising:
[0020] The substrate is sintered.
[0021] According to some embodiments of the present invention, the sintering temperature is 860° C.-960° C., and the sintering time is 60 min-120 min.
[0022] According to some embodiments of the present invention, the further comprising:
[0023] The substrate is boiled in water.
[0024] According to some embodiments of the present invention, the boiling water is boiled for 1 hour to 2 hours.
[0025] A vapor chamber according to a second aspect of the present invention includes:
[0026] The first surface includes a first dense groove area and a first sparse groove area alternately distributed along a first direction, and a second dense groove area and a second sparse groove area alternately distributed along a second direction, wherein the groove spacing in the first dense groove area is smaller than the groove spacing in the first sparse groove area, and the groove spacing in the second dense groove area is smaller than the groove spacing in the second sparse groove area.
[0027] The heat spreader according to the second aspect of the present invention has at least the following beneficial effects: the heat spreader has better hydrophilicity and can better distribute heat through the alternating distribution of the first dense groove area and the first sparse groove area.
[0028] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0030] Figure 1 A schematic diagram of the structure of a laser device used in a process for manufacturing a hydrophilic surface according to an embodiment of the present invention;
[0031] Figure 2 A schematic structural diagram of another embodiment of a laser device used in a process for manufacturing a hydrophilic surface according to an embodiment of the present invention;
[0032] Figure 3 A schematic diagram of processing a densely distributed substrate according to an embodiment of the present invention;
[0033] Figure 4 A schematic diagram of processing an alternating distribution type substrate according to an embodiment of the present invention;
[0034] Figure 5 Schematic diagram of the surface structure of a densely distributed substrate according to an embodiment of the present invention; wherein a) is a surface structure diagram at 500 μm, and b) is a surface structure diagram at 100 μm;
[0035] Figure 6 This is a schematic diagram of the surface structure of an alternating distribution type substrate according to an embodiment of the present invention; wherein a) is a surface structure diagram at 500 μm, and b) is a surface structure diagram at 100 μm;
[0036] Figure 7 It is a schematic diagram of test results of an alternating distribution type substrate and a dense distribution type substrate according to an embodiment of the present invention. The left side of the ruler in the figure is the alternating distribution type substrate, and the right side of the ruler in the figure is the dense distribution type substrate. DETAILED DESCRIPTION
[0037] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0038] In the description of the present invention, it should be understood that descriptions involving orientation, such as orientation or positional relationship indicated as up, down, etc., are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0039] In the description of the present invention, "a number" refers to one or more than one, and "a plurality" refers to two or more than two. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0040] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.
[0041] It should be noted that the surface of stainless steel itself has a certain hydrophilic property. After special treatment, the hydrophilic property of the stainless steel surface is further increased, making the hydrophilic property of the stainless steel surface better. In the related art, the special treatment method of stainless steel is to make a uniform and equally divided square groove structure on the surface of stainless steel, and to accommodate water molecules through the square groove structure, so that the contact angle between the water molecules and the stainless steel surface is reduced, thereby enabling the water molecules to climb along the stainless steel surface. The higher the climbing height, the better the hydrophilic property of the stainless steel. In this field, it is generally believed that the more uniform the square groove structure, the better the climbing performance of the stainless steel. Among them, the square groove structure refers to: a structure observed under a high-power microscope, which generally cannot be directly observed.
[0042] Reference Figures 1 to 7 As shown, an embodiment of the first aspect of the present invention proposes a process method for making a hydrophilic surface, comprising: laser processing the surface of a substrate along a first direction; wherein the laser processing area along the first direction includes alternatingly distributed first dense areas and first sparse areas, and the interval of the laser path in the first dense area is smaller than the interval of the laser path in the first sparse area.
[0043] Specifically, the laser device includes a laser source, a beam expander, a galvanometer, a field lens, and a stage. The laser source emits a laser beam, which passes through the beam expander, the galvanometer, and the field lens in sequence and is focused on the surface of the substrate on the stage to etch the surface of the substrate. The laser source may be a fiber laser or a solid-state laser, and a reflector may be provided as needed in the path of the laser beam so that the laser beam passes through the beam expander, the galvanometer, and the field lens in sequence according to a preset path.
[0044] In this embodiment, the laser beam is a nanosecond laser beam with a certain energy. After the laser beam is focused, a light spot with a certain energy and size is formed. This light spot is etched on the surface of the substrate on the stage by a galvanometer scanning method on the processing surface according to the drawing path in the software, thereby forming a structure of a certain morphology on the surface of the substrate. This structure will make the substrate super hydrophilic and liquid-absorbing.
[0045] Among them, the nanosecond laser needs to reach sufficient nanosecond laser power requirements, which is ≥50W in this solution. Its repetition rate range is 10KHz-3000KHz, and the pulse width is 100ns. The diameter of the reflector needs to be ≥25.4mm. If it is a fiber-type nanosecond laser, the spot diameter after collimation and before the incident galvanometer needs to be ≥10mm. The processing format of the galvanometer and field mirror is ≥ the required etching size, and the focused spot changes with the focal length of the field mirror and can be applied arbitrarily. Nanosecond lasers do not limit the wavelength, and each optical device changes with the wavelength of the nanosecond laser.
[0046] Nanosecond laser processing technology is also an important factor in preparing the hydrophilic surface of the material. The process includes nanosecond laser power, nanosecond laser repetition rate, pulse width, processing speed, filling shape, processing times and defocus. The nanosecond laser repetition rate and pulse width are based on ensuring the maximum output power of the nanosecond laser. In order to ensure processing efficiency, the number of processing times should be as small as possible but at least 1 time. In order to ensure processing quality, the defocus can be adjusted as needed, and to ensure etching depth, it can be set to 0mm.
[0047] After the laser is set, the laser focused spot moves along the preset path on the surface of the substrate. During the movement, the energy of the spot evaporates part of the material on the surface of the substrate, forming grooves on the microstructure. The grooves can improve the hydrophilicity of the substrate surface. In the related art, the smaller the grooves, the denser and more uniform the distribution, the better the hydrophilic effect of the substrate surface.
[0048] It should be noted that after laser processing, the grooves in the first dense area are densely distributed, and the grooves in the first sparse area are sparsely distributed. The first dense area and the first sparse area are alternately distributed. The substrate manufactured in this way is called an alternating distribution type substrate, such as Figure 4 and Figure 6 As shown in a) and b), the substrate manufactured entirely in the groove distribution manner in the first dense area is called a densely distributed substrate, such as Figure 3 and Figure 5 As shown in a) and b).
[0049] Further,
[0050] According to the common sense that the smaller the grooves, the denser and more uniform the distribution, the better the hydrophilic effect of the substrate surface, the hydrophilic property of the alternating distribution substrate should be lower than that of the densely distributed substrate.
[0051] However, if Figure 7 As shown, Figure 7 The left side of the middle ruler shows the climbing test results of the alternating distribution substrate. Figure 7 The right side of the middle ruler shows the climbing test results of the densely distributed substrate. Figure 7 The climbing test results of the alternating distribution substrate are significantly higher than Figure 7 The results of the climbing test of the medium-dense distribution type substrate show that the hydrophilicity of the alternating distribution type substrate is higher than that of the densely distributed type substrate.
[0052] Based on the above content, the following speculation is made: the densely distributed substrate has denser grooves, but too many grooves cause the structural superposition effect of the line conditions, resulting in crowded water channels and no free space reserved for water to climb out. Therefore, the climbing of water is restricted to a certain extent, which limits the hydrophilic performance of the densely distributed substrate.
[0053] Therefore, by laser processing the first dense area and the first sparse area, the laser path is distributed alternately dense and sparse, which reduces the structural superposition effect between the laser paths and reserves sufficient space for the climbing of water, thereby making the climbing ability of water better, and the hydrophilicity of the substrate is further improved, which is higher than the hydrophilicity of the dense substrate; moreover, the number of laser paths that the laser needs to travel is smaller, the laser processing efficiency is higher, and the production efficiency is higher.
[0054] Reference Figure 3 and Figure 4 As shown, in some specific embodiments of the present invention, the processing spacing of the first dense area is 1L-3L; the processing spacing of the first sparse area is 6L-10L; L: the spot diameter after laser focusing.
[0055] Furthermore, in this embodiment, the spot diameter of the laser focus is 0.05mm-0.07mm, the processing spacing of the first dense area is 1.5L, so the processing spacing of the first dense area is 0.075mm-0.105mm, and the processing spacing of the first sparse area is 10L, so the processing spacing of the first sparse area is 0.5mm-0.7mm.
[0056] In this embodiment, the number of grooves in a single first dense area is 4, and the number of grooves in a single first sparse area is 1. The first sparse area is formed by the interval between the two first dense areas. The first sparse area is not processed by laser, but is formed by the interval between the two first dense areas, so that the laser only needs to process the grooves within the first dense area, and the laser does not need to be adjusted. In addition, the number of processed grooves is smaller, so the laser processing efficiency is higher, and the alternating distribution type substrate can be produced more efficiently. Among them, the surface of the processed substrate is as follows Figure 6 As shown in a) and b).
[0057] Reference Figure 3 and Figure 4 As shown, in some specific embodiments of the present invention, the process for making a hydrophilic surface further includes:
[0058] The laser processes the surface of the substrate along a second direction;
[0059] The second direction is perpendicular to the first direction, and the laser processing area along the second direction includes alternately distributed second dense areas and second sparse areas, and the interval of the laser paths in the second dense areas is smaller than the interval of the laser paths in the second sparse areas.
[0060] It is worth understanding that, through laser processing along the second direction, the criss-cross grooves are formed into a plurality of square grooves. The microstructure of the square grooves can better improve the hydrophilicity of the substrate surface.
[0061] In this embodiment, the square grooves are formed by the laser moving crosswise along the first direction and the second direction to produce sufficient microscopic morphology, but the line spacing of the laser movement needs to be designed to a certain extent, which is particularly important for improving processing efficiency. Although nanosecond laser processing of the substrate in a densely distributed manner can also obtain good hydrophilic and climbing properties, in order to improve processing efficiency and further improve hydrophilic properties, the laser trajectory needs to be designed according to Figure 4 The alternating distribution method is the most efficient for processing substrates, and the optimal laser etching speed is 83mm 2 / s. The specific etching track is as follows Figure 4 As shown in the figure, the nanosecond laser trajectory is first horizontal and then vertical, where the vertical direction is the direction of liquid absorption and climbing. The surface of the processed substrate is as follows Figure 6 As shown in a) and b).
[0062] In some specific embodiments of the present invention, the moving speed of the laser is 500 mm / s-2000 mm / s.
[0063] In this embodiment, the nanosecond laser power is selected to be full power output, and the processing speed needs to be selected according to the requirements or as high as possible to improve the processing efficiency. Usually, in order to improve efficiency, the processing speed will pursue high speed, but when the laser processing speed is greater than a certain speed, the climbing height drops sharply. This solution is 500mm / s-2000mm / s, generally 1000mm / s, the processing number is 1, and the equivalent laser etching speed is 55mm 2 / s, compared with other etching methods, it has shorter cycle time and higher productivity.
[0064] In some specific embodiments of the present invention, the process for making a hydrophilic surface further comprises:
[0065] Sintering the substrate.
[0066] Furthermore, the sintering temperature is 860° C.-960° C., and the sintering time is 60 min-120 min.
[0067] It is worth understanding that high temperature sintering of the substrate can reinforce the laser etching, making the hydrophilic surface of the substrate more stable.
[0068] In some specific embodiments of the present invention, the process for making a hydrophilic surface further comprises:
[0069] Boil the substrate in boiling water.
[0070] Furthermore, the boiling water is boiled for 1h-2h.
[0071] It is worth understanding that the surface of the substrate after boiling water is more likely to adhere to water, and after being placed for a long time and then tested, it can still have good hydrophilic properties.
[0072] For ease of understanding, a specific embodiment is used as an example below for illustration:
[0073] First, a nanosecond laser is used. The laser beam emitted by the nanosecond laser passes through a beam expander, a reflector group, a high-speed galvanometer, and a large-format field mirror to form a light spot with a certain energy and size.
[0074] Comparative Example
[0075] The parameters of the nanosecond laser are power 100W, repetition rate 100KHz, pulse width 100ns, the movement speed of the laser spot relative to the substrate is 1000mm / s, the number of processing times is 1, the spot diameter is L, and it moves in the second direction with a processing spacing of 1.5L, and then moves in the first direction with a processing spacing of 1.5L, wherein the first direction is the liquid absorption and climbing direction, and a densely distributed substrate is obtained.
[0076] Example
[0077] The parameters of the nanosecond laser are power 100W, repetition rate 100KHz, pulse width 100ns, the movement speed of the laser spot relative to the substrate is 1000mm / s, the number of processing times is 1, the spot diameter is L, and it moves in the second direction with a processing spacing of 10L, and then moves in the first direction with a processing spacing of 1.5L, wherein the first direction is the liquid absorption and climbing direction, to obtain an alternating distribution type substrate.
[0078] test
[0079] The alternating distribution substrate and the dense distribution substrate were placed in water at the same time, and the results were as follows: Figure 7 As shown, the climbing height of the alternating distribution type substrate is about 73mm-6mm=67mm, and the climbing height of the densely distributed type substrate is about 53mm-5mm=48mm. It can be seen that the climbing height of the alternating distribution type substrate is increased by 39.5% compared with the climbing height of the densely distributed type substrate, and the hydrophilic performance of the alternating distribution type substrate is significantly improved.
[0080] A second embodiment of the present invention provides a vapor chamber, comprising: a first surface,
[0081] The first surface includes a first dense groove area and a first sparse groove area alternately distributed along a first direction, and a second dense groove area and a second sparse groove area alternately distributed along a second direction, wherein the groove spacing in the first dense groove area is smaller than the groove spacing in the first sparse groove area, and the groove spacing in the second dense groove area is smaller than the groove spacing in the second sparse groove area.
[0082] In this embodiment, other surfaces of the heat spreader may also have the surface structure of the first surface to make the overall hydrophilicity of the heat spreader better. Among them, the number of grooves in the first dense groove area is 4, and the number of grooves in the first sparse groove area is 1. The first sparse groove area does not need to be processed by laser, but is directly formed by two adjacent first dense groove areas to improve the processing efficiency of the first surface of the heat spreader. The number of grooves in the second dense groove area is also 4, and the number of grooves in the second sparse groove area is 1. It is worth understanding that the heat spreader has better hydrophilicity and can better distribute heat through the alternating distribution of the first dense groove area and the first sparse groove area.
[0083] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A process for making a hydrophilic surface, characterized in that: include: The laser processes the surface of the substrate along a first direction; The laser processing area along the first direction includes a first dense area and a first sparse area that are alternately distributed, and the interval between laser paths in the first dense area is smaller than the interval between laser paths in the first sparse area.
2. The process for producing a hydrophilic surface according to claim 1, characterized in that: The processing spacing of the first dense area is 1L-3L; The processing spacing of the first sparse area is 6L-10L; L: The spot diameter of the laser after focusing.
3. The process for making a hydrophilic surface according to claim 1, characterized in that: The processing spacing of the first dense area is 0.075mm-0.105mm; The processing spacing of the first sparse area is 0.5mm-0.7mm.
4. The process for making a hydrophilic surface according to claim 1, characterized in that: Also includes: The laser processes the surface of the substrate along a second direction; The second direction is perpendicular to the first direction, the processing area of the laser along the second direction includes a second dense area and a second sparse area that are alternately distributed, and the interval between the laser paths in the second dense area is smaller than the interval between the laser paths in the second sparse area.
5. The process for making a hydrophilic surface according to claim 1, characterized in that: The moving speed of the laser is 500mm / s-2000mm / s.
6. The process for making a hydrophilic surface according to claim 1, characterized in that: Also includes: The substrate is sintered.
7. The process for producing a hydrophilic surface according to claim 6, characterized in that: The sintering temperature is 860° C.-960° C., and the sintering time is 60 min-120 min.
8. The process for making a hydrophilic surface according to claim 6, characterized in that: Also includes: The substrate is boiled in water.
9. The process for producing a hydrophilic surface according to claim 8, characterized in that: The boiling water is boiled for 1h-2h.
10. A heat spreader, characterized in that: include: The first surface includes a first dense groove area and a first sparse groove area alternately distributed along a first direction, and a second dense groove area and a second sparse groove area alternately distributed along a second direction, wherein the groove spacing in the first dense groove area is smaller than the groove spacing in the first sparse groove area, and the groove spacing in the second dense groove area is smaller than the groove spacing in the second sparse groove area.